Economic Analysis Of Production And Marketing Of Mushrooms - Renjith Raja R (Department of Agricultural Economics, College of Horticulture, 2000)
The present study entitled the Economics of Production and Marketing of Mushroom was undertaken during the year 1999-2000. This study was conducted in Thiruvananthapuram district. This district was purposely selected for the study because mushroom growmg units on commercial basis are well established ill Thiruvananthapuram district. A sample of 100 growers who maintained contact with the training centres was selected. Each farmer was interviewed personally. Among the 100 sample farmers 36 were cultivating mushrooms and the remaining had given up cultivation. All the mushroom growers were post-stratified on the basis of nature of investment into Category-I (Temporary upto Rs.15000 ), Category-IT (Semi-permanent Rs.15000-25000) and Category-Ill (Permanent above Rs.25000) Tabular analysis was used to study the socio-economic features, to estimate the cost and returns, marketing cost and margins of mushrooms. Cost concepts were used to estimate the income measures. At aggregate level the total cost incurred for cultivation of mushroom was Rs. 8167.83. Material inputs accounted for about 82.85 per cent of the total working capital requirement for the sample as a whole. Hired labour component was absent in category-I. At aggregate level this accounted for 17.15 per cent total working capital requirement. Total working capital requirement for mushroom production was Rs. 3738.51. As compared to males, females were more in the working force, which shows the women's participation in mushroom cultivation. Explicit costs accounted for 45.77 percent of the total cost. Implicit cost accounted for 54.23 per cent of the total cost. Cost A], Bj, Cl, and C3 per crop cycle for the sample as a whole was Rs. 4144.95, Rs. 4522.91, Rs. 1425.30 and Rs. 8167.83. The total working capital requirement for producing 1 kilogram of spawn was Rs. 12.83. Explicit cost accounted for 71.60 per cent of the total cost. Implicit cost